Competitiveness analyses of Indonesian and Malaysian palm oil exports - Tri Nugraha Ramadhani; Rokhedi Priyo Santoso (Universitas Islam Indonesia, 2019)
This study investigates the competitiveness of Indonesian and Malaysian palm oil export with special focus on five major importing countries, namely China, Singapore, India, Pakistan, and Netherlands, from 2001 to 2014. The methods used are Revealed Comparative Advantage (RCA), Revealed Symmetric Comparative Advantage (RSCA) and Constant Market Share (CMS). Findings/Originality: The RCA and RSCA calculations show that Indonesia and Malaysia have positive indices. Yet, Indonesia's RCA and RSCA indices from 2001 to 2014 are higher than those of Malaysia. It demonstrates that Indonesia's palm oil is more competitive than that of Malaysia. Based on CMS calculation, the findings show the following. Firstly, palm oil commodity is influenced by high demand from 2001 to 2014 in five major importing countries. Secondly, both countries have concentrated on the export commodity whose markets have been growing relatively fast. Thirdly, Indonesia's palm oil commodity experiences rapid growth in the selected markets while Malaysia experiences stagnant growth. Overall, Indonesia's palm oil competitiveness is higher than that of Malaysia in five major importing countries.